VISUALISASI NILAI-NILAI PRANAYAMA DALAM KARYA SENI PATUNG ABSTRAK - Merta, I Dewa Putu (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2021)
This article is the creation of research-based works related to the values of Pranayama. Pranayama is one of the yoga activities that puts more emphasis on breathing, body movement and is combined with concentration. There is a holy relationship or a combination of breathing, body work and concentration which can create a balance between body and soul (subtle body and gross body). The union between body and soul can occur when the combination of breath, body movement (hand movement), and concentration. The meaning contained in pranayama tantra is balance. This theme is taken from a meaning contained in tantra pranayama. The emergence of this theme explicitly refers to the object itself based on the fact that an artist has a sense of sensitivity in observing, dismantling, and peeling off an object as a source of inspiration. The method of creation is a method developed by Hawkins to create works of art systematically. The stages of creating an art work that outlines the design process for the creation of an art work according to the stages of the work, from the inspiration (idea) to the design, to the embodiment of the artwork. By cultivating the balance value contained in tantra pranayama it is visually manifested into three-dimensional works of art. The concept of space and field is the basis for visualizing it, so that it can give birth to monumental abstract sculptures.